A dyadic study of psychological well-being of individuals with Parkinson’s disease and their caregivers - Lee, Y; Chiou, Y-J; Hung, C-F; Chang, Y-Y; Chen, Y-F; Lin, T-K; Wang, L-J (Springer Nature, 2021)
Parkinson's disease (PD) is an incapacitating neurodegenerative disease. Patients with PD and their caregivers may have interactive effects on each other’s psychological well-being. This study aimed to assess the dyadic dynamics of resilience, fatigue, and suicidal ideation on the depression severity of PD patients and their caregivers. In total, 175 PD patients and 175 caregivers were recruited at a medical center from August 2018 to May 2020. Structural equation modeling (SEM) was used to examine the actor/partner effects on the psychological well-being of both the PD patients and their caregivers. The most common psychiatric diagnoses of both the PD patients (28.6%) and their caregivers (11.4%) were depressive disorders. The PD patients’ and their caregivers’ fatigue, suicidal ideation, and lack of resilience were significantly associated with the severity of their depression, respectively. Interactive effects existed between psychological well-being of individuals with PD and their caregivers. Clinicians must be aware of, and manage, these contributing factors between PD patients and their caregivers in order to prevent them from worsening each other’s depression.